ANÁLISE DA COMPOSIÇÃO QUÍMICA EM VARIEDADES DE BERILO, POR ATIVAÇÃO NEUTRÔNICA INSTRUMENTAL (INAA) - Polli, G. O.; Oliveira, E. F.; Sabioni, A. C. S.; Ferreira, A. C. M.; Roeser, H. M. P. (Geochimica Brasiliensis, 2012)